Secreted Frizzled - related Protein 4 y el cáncer de mama - José María Gálvez-Navas; Cristina Pérez-Ramírez; M Carmen Ramírez-Tortosa (Ars Pharmaceutica, 2021)
Abstract Introduction: cell's correct functionality and surveillance are brokered by a wide range of essential proceedings. The delicate equilibrium required between those phenomenon means that an error in the control mechanisms provoke the carcinogenesis commencement. In those metabolic pathways in charge of controlling the mechanisms are found the Wnt signaling pathways. Therefore, molecules that interact with the pathways mentioned, where secreted Frizzled - Related Protein 4 is located, will play a key role in the pathology knowledge. Method: a bibliographic research has been done in referral databases, such as Medline and Scopus. Results: sFRP4 has been identified as a negative modulator of the Wnt signaling pathways. This is due to its capacity of competing for the Wnt ligands and avoiding the commencement of the pathways. Otherwise, sFRP4 is essential for the control of the cancer beginning and development in those tissues where the protein is expressed, being mammary tissues considered into them. Conclusions: recent studies about the implications of sFRP4 in the development of several pathologies justify that the protein had garnered attention in recent years. Furthermore, it can be affirmed that sFRP4 presents an interesting potential as biomarker in the breast cancer treatment, diagnosis and prognosis, among other pathologies.